(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article придает describes the способствует impact of corporate культуры culture on management inst effectiveness, the main управления mechanisms of its составляющая formation, and долгосрочной identifies diagnostic этапе methods and management определяется managemtnmm manatools of цof oforganizational участие culture of modern человеческие enterprises.